ANALYSIS OF RESEARCH ON PHYSICAL CHEMICAL COMPOSITION AND CLASSIFICATION OF WOOL FIBER (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the physico-chemical composition, structure, classification, types, fields of application and similar indicators of wool fiber.